Yield behavior of hybrid maize Agri-104 on different sowing systems, densities and localized irrigation - León Aguilar, Rolando (2018)
This research aimed to evaluate the yield behavior of mayze (Zea mays L.) hybrid AGRI-104 at different densities and sowing systems under localized irrigation. The research was carried out on the experimental campus “La Teodomira” of the faculty of Agronomic Engineering of the Technical University of Manabí, Ecuador, between July and December of 2016. A randomized complete block design with six treatments and three replicates was applied in a factorial arrangement. The factors subject of study were sowing systems (hand and ploughed), sowing density (0,40; 0,70 y 0,90 m between rows). The assessed variables were: length and depth of the wet bulb, root system development, as well as a set of morpho-physiological and yield variables. An analysis of variance (ANOVA) was carried out through the statistical package StatGraphics Centurion XV.II v16.1.18 and means were compared with Tukey (p<0,05). Wet bulb reached with localized irrigation ensured appropriate conditions for the development of the root system of the plants sown both ploughed and without ploughed. Sowing density has a significant effect on plants length. Sowing systems and densities had a significant influence on the yield of hybrid mayze AGRI 104.